Innovation beyond firm boundaries: an introduction - von Krogh, Georg (Henry Stewart Talks, 2011)
Open business models, Closed innovation, Open innovation, Challenges, The private model, The collective model, The generic incentive structure, Experimental results on knowledge sharing, Strategies to motivate customers, Degree of openness, The Nokia study, Applications developed, Benefits of innovation beyond firm boundaries, Costs, A strategy change